Enhanced electrocatalytic activity of palladium nanochains by modifying transition metal core-shell nanoparticles (TMcore-shell = Ni@NiO, Co@CoO) on reduced graphene oxide for methanol electro-oxidation. (20th October 2019) - He, Qiugu; Zhang, Qiao; Yang, Xikun; Zhang, Chengxu; Zeng, Xiaoyuan; Shi, Jin; Li, Mian; Zhang, Yingjie; Xu, Mingli
Abstract: Palladium nanochains with uniform dispersion supported transition metal core-shell nanoparticles (TMcore-shell, TMcore-shell = Ni@NiO, Co@CoO) modified reduced graphene oxide (rGO) are synthesized through a facile two-step method as the catalysts for methanol electro-oxidation. The transition metal nanoparticle consists of transition metal core and transition metal oxide shell layer with an average particle diameter of about 35 nm, which can play an important role in adjusting the electronic structure of Pd. It can be attributed to the different support-metal synergistic interaction (SMSI) between TMcore-shell -rGO support and Pd metal. In addition, the Pd/Co@CoO-rGO catalyst exhibits the highest electrocatalytic activity for methanol electro-oxidation, with the mass activity of 1786 mA mg −1, which is 7.01 times and 1.49 times as high as those of the commercial Pd/C and the commercial Pt/C, respectively. Furthermore, the Pd/Co@CoO-rGO catalyst keeps the best stability than the commercial Pd/C, the commercial Pt/C, Pd/rGO and Pd/Ni@NiO-rGO catalysts during all the test time. TMcore-shell -rGO support provide us a new strategy of structure engineering for highly efficient methanol oxidation. Highlights: A novel Pd/TMcore-shell -rGO hybrid electrocatalyst is prepared by a facile two-step method. The electro-catalytic activity of Pd/Co@CoO-rGO catalyst is 7.01 times as high as that of the commercial Pd/C. The enhanced electro-catalytic activity could be attributed to the support-metal synergistic interaction. The Pd/Co@CoO-rGO catalyst will be a very promising catalyst in the commercialization of the alkaline DMFCs in future.